Human Alphacoronavirus Universal Primers for Genome Amplification and Sequencing - Choi, Sungmi; Kim, Kwan Woo; Ku, Keun Bon; Kim, Seong-Jun; Park, Changwoo; Park, Dongju; Kim, Seil; Yi, Hana (Frontiers in Microbiology, 2022)
Rapid and accurate sequencing covering the entire genome is essential to identify genetic variations of viral pathogens. However, due to the low viral titers in clinical samples, certain amplification steps are required for viral genome sequencing. At present, there are no universal primers available for alphacoronaviruses and that, since these viruses have diverse strains, new primers specific to the target strain must be continuously developed for sequencing. Thus, in this study, we aimed to develop a universal primer set valid for all human alphacoronaviruses and applicable to samples containing trace amounts of the virus. To this aim, we designed overlapping primer pairs capable of amplifying the entire genome of all known human alphacoronaviruses. The selected primers, named the AC primer set, were composed of 10 primer pairs stretching over the entire genome of alphacoronaviruses, and produced PCR products of the expected size (3–5 kb) from both the HCoV-229E and HCoV-NL63 strains. After genome amplification, an evaluation using various sequencing platforms was carried out. The amplicon library sequencing data were assembled into complete genome sequences in all sequencing strategies examined in this study. The sequencing accuracy varied depending on the sequencing technology, but all sequencing methods showed a sequencing error of less than 0.01%. In the mock clinical specimen, the detection limit was 10−3 PFU/ml (102 copies/ml). The AC primer set and experimental procedure optimized in this study may enable the fast diagnosis of mutant alphacoronaviruses in future epidemics.